Conservation practitioners' understanding of how to manage evolutionary processes. Issue 5 (1st April 2019) - Cook, Carly N.; Sgrò, Carla M.
Abstract: Both academics and practitioners consider a lack of knowledge about evolutionary theory to be a general barrier to effectively managing genetic diversity. However, it is challenging to judge practitioners' level of understanding and how this influences their management decisions. Knowledge built through experience may be difficult for practitioners to articulate, but could nonetheless result in appropriate management strategies. To date, researchers have assessed only the explicit (formal) knowledge practitioners have of evolutionary concepts. To explore practitioners' understanding of evolutionary concepts, it is necessary to consider how they might apply explicit and implicit knowledge to their management decisions. Using an online survey, we asked Australian practitioners to respond to 2 common management scenarios in which there is strong evidence that managing genetic diversity can improve outcomes: managing small, isolated populations and sourcing seeds for restoration projects. In describing their approach to these scenarios, practitioners demonstrated a stronger understanding of the effective management of genetic diversity than the definitions of the relevant concepts. However, their management of genetic diversity within small populations was closer to best practice than for restoration projects. Moreover, the risks practitioners described in implementing best practice management were more likely to affect their approach to restoration than translocation projects. These findings provide evidence that strategies to build the capacity of practitioners to manage genetic diversity should focus on realistic management scenarios. Given that practitioners recognize the importance of adapting their practices and the strong evidence for the benefits of actively managing genetic diversity, there is hope that better engagement by evolutionary biologists with practitioners could facilitate significant shifts toward evolutionarily enlightened management. Abstract : Article impact statement : Better engagement with practitioners could facilitate significant shifts toward evolutionarily enlightened management. Abstract : Entendimiento de los Practicantes de la Conservación sobre Cómo Manejar los Procesos Evolutivos Resumen: Tanto los académicos como los practicantes consideran que una falta de conocimiento sobre la teoría evolutiva es una barrera general para el manejo efectivo de la diversidad genética. Sin embargo, es complicado juzgar el nivel de entendimiento de los practicantes y cómo éste influye sobre sus decisiones de manejo. El conocimiento construido por medio de la experiencia puede ser difícil de articular para los practicantes, pero de igual manera podría resultar en estrategias adecuadas de manejo. A la fecha, los investigadores han evaluado solamente el conocimiento explícito (formal) que tienen los practicantes sobre los conceptos evolutivos. Para explorar el entendimiento que tienen los practicantes sobre los conceptos evolutivos es necesario considerar cómo podrían aplicar conocimientos explícitos e implícitos a sus decisiones de manejo. Por medio de una encuesta en línea, le pedimos a practicantes australianos que respondieran a dos escenarios comunes de manejo en los cuales hay fuertes evidencias de que el manejo de la diversidad genética puede mejorar los resultados: el manejo de poblaciones pequeñas y aisladas, y la obtención de semillas para proyectos de restauración. Cuando describieron sus métodos para estos escenarios, los practicantes demostraron tener un entendimiento más completo del manejo efectivo de la diversidad genética que de las definiciones de los conceptos relevantes. Sin embargo, su manejo de la diversidad genética dentro de poblaciones pequeñas estuvo más cerca de la mejor práctica que para los proyectos de restauración. Además, los riesgos que los practicantes describieron en la implementación del manejo de la mejor práctica tuvieron una mayor probabilidad de afectar a sus estrategias de restauración que a las de reubicación. Estos resultados proporcionan evidencia de que las estrategias para construir la capacidad de los practicantes para manejar la diversidad genética deben enfocarse en escenarios realistas de manejo. Ya que los practicantes reconocen la importancia de adaptar sus prácticas y reconocen la sólida evidencia para los beneficios del manejo activo de la diversidad genética, hay esperanzas de que una mejor colaboración entre los practicantes y los biólogos evolutivos pudiera facilitar cambios significativos hacia un manejo informado evolutivamente. 摘要: 研究者和保护实践者都认为, 进化理论知识的缺乏常常会阻碍对遗传多样性的有效管理。然而, 判断保护实践者对进化理论的理解程度及其对他们的管理决策的影响却极具挑战。对于保护实践者来说, 通过经验积累的知识可能难以阐述, 但仍然可以指导他们采取合适的管理策略。到目前为止, 研究者只评估过保护实践者关于进化概念的显性知识 (形式知识) 。为探究保护实践者对进化概念的理解, 还应考虑他们如何将显性及隐性知识应用于管理决策。我们通过在线调查, 收集了澳大利亚保护实践者对两种常见管理情景的反应, 在这两种情景 (管理小的隔离种群、追溯恢复计划中引种来源) 中, 均有证据表明管理遗传多样性可以提高保护成效。从实践者对管理这些情景的方法描述中可以看出, 他们对遗传多样性有效管理的理解比对相关概念定义的理解更深刻。然而, 相比于恢复项目, 实践者对小种群遗传多样性的管理方法更接近最佳实践。此外, 他们描述的最佳实践实施中的风险更有可能影响他们对恢复项目的管理方法, 而不是影响迁地保护项目。这些发现证明, 提升保护实践者管理遗传多样性能力的策略应侧重于现实中的管理场景。考虑到保护实践者已经认识到合理调整保护实践的重要性, 且积极管理遗传多样性大有裨益, 我们呼吁进化生物学家应更多地参与保护实践, 以促进保护管理在进化理论应用上的重要转向。【翻译: 胡怡思; 审校: 聂永刚】